CROSS-LINGUISTIC INFLUENCES BETWEEN UZBEK AND ENGLISH LANGUAGES - Abdumurodova Sevinch To‘raqulovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract.This study investigates cross-linguistic influences between two languages, Uzbek and English, in full scope. The article’s significance lies in its contribution to facilitating the learning process for both language learners. This research aims to answer two key questions “ What is the use of learning the cross-linguistic differences and influences between those languages ? ” and “ What kind of distinguishable features do they capture at all? ” The study identifies common challenges students encounter in the learning process, especially in grammar, pronunciation, and vocabulary. A better understanding of these linguistic differences can help enhance teaching strategies and improve language acquisition.